Barriers and missed opportunities in PrEP uptake, use and care among men who have sex with men with recent HIV infection in the Netherlands - Jeffrey C. D. Koole; Maarten R. D. Bedert; Feline de la Court; Irene Bais; Ferdinand Wit; Janneke Stalenhoef; Tania Mudrikova; Katalin Pogany; Birgit van Benthem; Maria Prins; Udi Davidovich; Marc van der Valk (PLoS ONE, 2025)
Introduction Oral pre-exposure prophylaxis (PrEP) prevents Human Immunodeficiency Virus (HIV) acquisition. In the Netherlands, PrEP is accessible through the national PrEP program (NPP) or general practitioners (GP). Still, some men who have sex with men (MSM) entering HIV care indicated having PrEP experience prior to diagnosis. We aimed to identify barriers and missed opportunities in PrEP uptake, care and use among MSM with HIV and previous PrEP experience. Methods Between March 2022-March 2023, we conducted semi-structured in-depth interviews on PrEP among MSM diagnosed with HIV from 2019 onwards with previous PrEP experience. Interviewees were recruited through their HIV treatment centers and social media. Results Of the 11 included MSM, most reported significant PrEP-uptake delay because of the limited NPP capacity and high threshold of accessing PrEP from GPs (e.g. stigma, lack of sexual health expertise). Additional uptake or use barriers included anticipated/experienced side-effects, burden of daily pill-taking or event-driven regimen complexity, the latter leading to PrEP discontinuation. Missed opportunities in counseling on adherence and safer sex alternatives after discontinuation were reported. Most interviewees considered informal PrEP unsuitable. Conclusion PrEP uptake delay played a crucial role in context of HIV infection among MSM with HIV and previous PrEP experience. HIV diagnoses at or shortly after PrEP initiation emphasize the importance of ensuring rapid and timely PrEP access. Uptake barriers at GPs, stigma on sexuality, lack of expertise, and missed care opportunities need to be addressed. Early detection of PrEP protocol/user-mismatch and counseling on safer sex alternatives after discontinuation are pivotal for sustainable HIV prevention.